2016
DOI: 10.1136/neurintsurg-2015-012084
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular optical coherence tomography for the evaluation of arterial bifurcations covered by flow diverters

Abstract: Intravascular OCT appears to be a promising technique for immediate and follow-up assessment of the orifice of arterial branches covered by flow diverting stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…These observations support the hypothesis that side branch remodelling after flow diversion is a hemodynamic process of constant re-adaptation, which can potentially evolve either way, not only toward progressive occlusion but also toward limiting endothelial coverage. 15,17 Similar to our results, other recent publications have shown good clinical and anatomic results with flow diverters for MCA bifurcation aneurysms. Zanaty et al, 13 in their series of complex large, giant, and bifurcation MCA aneurysms treated with the PED, reported its effectiveness with reasonable complication rates.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These observations support the hypothesis that side branch remodelling after flow diversion is a hemodynamic process of constant re-adaptation, which can potentially evolve either way, not only toward progressive occlusion but also toward limiting endothelial coverage. 15,17 Similar to our results, other recent publications have shown good clinical and anatomic results with flow diverters for MCA bifurcation aneurysms. Zanaty et al, 13 in their series of complex large, giant, and bifurcation MCA aneurysms treated with the PED, reported its effectiveness with reasonable complication rates.…”
Section: Discussionsupporting
confidence: 81%
“…Recent laboratory data showed that terminal-type arteries, when jailed, tend to maintain poststenting flow rates similar to the prestenting ones in the acute poststenting phase; this scenario, in turn, seems related to decreased neointimal coverage of the jailed ostia at 3-month control. [15][16][17] In accordance with previous reports, transient symptoms were noted during the first follow-up months. 18 In our opinion, they were not related to in situ thrombotic events but rather to hemodynamic parameters.…”
Section: Discussionsupporting
confidence: 77%
“…In animal models, OCT has been used to assess PED wall apposition 9 and side branches covered by the PED. 10,11 We are not aware of any prior use of OCT after PED placement in humans.…”
Section: Potential Mechanisms Underlying the Collar Signmentioning
confidence: 99%
“…Increased neointimal thickness at the level of branching artery ostia in the presence of competitive collateral circulation had been recently demonstrated in a pig model using optic coherence tomography (OCT) and scanning electron microscopy (SEM). 22 Two subjects had mild narrowing of the parent artery just proximal to the implant seen on an early follow-up angiogram, without flow limitation or clinical consequences. On 6-mo follow-up angiogram, this had resolved, suggesting this may be a transient remodeling process.…”
Section: × 12 MM Pipeline Embolization Device (Arrows On Proximal and Distal Device Markers) Was Advanced Into The Callosmarginal Artery mentioning
confidence: 93%